Seni Melawan Pedagang Asongan di Kereta Api Lokal Ekonomi Merak-Rangkasbitung Banten - Musahwi Musahwi; Minnati Zulfa Anika; Pitriyani Pitriyani (Simulacra, 2018)
This study attempts to uncover the resistance of hawkers against the prohibition of selling at stations and trains by taking the locus of Merak-Rangkasbitunglocal train. Specifically the purpose of this study is to uncover the daily hidden resistance that is concealed by hawkers. This kind of resistance model refers to Scott's concept from his theory which is the domination of the art of resistance or noted by the weapon of the weak againts of the elite or the policies which opressed them. In this study, used the qualitative-phenomenology methods. This approach is chosen to reveal the phenomena based on the perspectives of those who experience them directly, with an in-depth expression of the phenomenon of consciousness within them during resistance. The results of this study include: a) disobedience (keepselling) against the law by pretending not to know. b) sellingpretend as passengers. c) negotiating "as if" with the officer, meaning they end up violating, and d) resisting the ban on selling by rebel. The daily, unorganized and invidual resistance to this is done because there is no alternative to the economic solution for them; they have no capital; social, educational, and political. They are weak people, and according to them are increasingly weakened by the policy of the ban.